Extreme climate and crime: Empirical evidence based on 129 prefecture-level cities in China - Peng, Jiquan; Zhan, Zhijun (Frontiers in Ecology and Evolution, 2022)
Climate change is having profound effects on natural and socio-economic systems, especially via extreme climate events. Using panel data from 129 prefectural-level cities in China from 2013 to 2019, this paper explores the effects of extreme climate on crime rates based on a climate index and manual collection of crime data. The results showed that extreme climate has a significant positive effect on crime rates, increasing by 0.035% for every 1% increase in the extreme climate index. This occurs through two mechanistic pathways: reduced agricultural output and lower employment income. The heterogeneity analysis shows that extreme climate has a greater impact on crime rates in eastern areas which are economically developed and have high levels of immigration. This study provides new perspectives on the impact of extreme climate on the economy and society and discusses how the government can reduce its impact on crime through appropriate climate-based interventions.